Mycobacterium Species on the Cutaneous Microbiome of Very Preterm Neonates. (27th February 2022) - Shah, Pritik A; Govindarajan, Varun; Rangaiah, Ambica; Diggikar, Shivashankar; Devadas, Sahana; Chunchanur, Sneha K; Shankar, Sathyanarayan Muthur; Das, Subhadeep; Kariyappa, Mallesh
Abstract: The neonatal skin microbiome consists of all the genomes and genetic products of microorganisms harboring on an infant's skin. Host and the microbiota develop a harmonious environment resulting in symbiosis. Any disruption of this environment could lead to pathological disease. This study was conducted to understand the neonatal skin microbiome of very preterm neonates (under 32 weeks) admitted to the Neonatal Intensive Care Unit(NICU) at a tertiary healthcare setting before and after kangaroo mother care (KMC), using next-generation sequencing (NGS). Skin swabs were collected on two different occasions and analyzed using the NGS technique after amplification via polymerase chain reaction. The results showed relative abundance for Mycobacterium tuberculosis in 83.33% and 66.67% ( p = 0.29 ) and Mycobacteroides abscessus in 100% and 93.33% ( p = 0 .30 ) of the very preterm neonates on the skin microbiome before and after KMC, respectively as an incidental finding. The mere presence of these bacilli as commensals or as potential pathogens is alarming due to the risk of early exposure and incidence of tuberculosis from birth. These findings, in our view, are the first findings to be established in such a setting.